2015
DOI: 10.1007/s13437-014-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of port authorities in the development of LNG bunkering facilities in North European ports

Abstract: Liquefied natural gas (LNG) serves as an attractive fuel for ships to meet the upcoming stringent environmental regulations enacted by IMO, particularly at the level of emission control areas (ECA). The use of LNG promises a good environmental performance and a foreseeable economic viability. However, a general absence of bunkering infrastructure in seaports is a significant barrier currently preventing the breakthrough of the use of LNG as a ship fuel. Against this backdrop, we observe that public port author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Port authorities, who are responsible for managing the landside and seaside of ports, can play important roles in facilitating environmental upgrading (Chang and Wang, 2012;Giuliano and Linder, 2013, Merk, 2014, Gibbs et al, 2014, Davarzani et al, 2015, Erdas et al 2015, Wang and Notteboom, 2015, Styhre et al, 2017 through four key functions they perform: (1) as landlords (providing land and basic infrastructure); (2) as regulators (setting tariffs, environmental standards for tenants and other port users, and engaging in spatial planning); (3) as operators (having their own fleets of harbor craft and equipment to provide safe fairways and basic infrastructure); and 4as community managers (bringing together a variety of port stakeholders to improve collaboration and port performance) (Verhoeven, 2010, Acciaro et al, 2014a. An array of organizational and technological tools available to port authorities has already been identified, including pricing and incentives, monitoring and measuring, market access control, environmental standards regulation, alternative energy supply and demand, and a range of emission reducing technology (Solomon and Bailey, 2004, Lam and Notteboom, 2014, Gibbs et al, 2014, Acciaro et al, 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…Port authorities, who are responsible for managing the landside and seaside of ports, can play important roles in facilitating environmental upgrading (Chang and Wang, 2012;Giuliano and Linder, 2013, Merk, 2014, Gibbs et al, 2014, Davarzani et al, 2015, Erdas et al 2015, Wang and Notteboom, 2015, Styhre et al, 2017 through four key functions they perform: (1) as landlords (providing land and basic infrastructure); (2) as regulators (setting tariffs, environmental standards for tenants and other port users, and engaging in spatial planning); (3) as operators (having their own fleets of harbor craft and equipment to provide safe fairways and basic infrastructure); and 4as community managers (bringing together a variety of port stakeholders to improve collaboration and port performance) (Verhoeven, 2010, Acciaro et al, 2014a. An array of organizational and technological tools available to port authorities has already been identified, including pricing and incentives, monitoring and measuring, market access control, environmental standards regulation, alternative energy supply and demand, and a range of emission reducing technology (Solomon and Bailey, 2004, Lam and Notteboom, 2014, Gibbs et al, 2014, Acciaro et al, 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…In the past five years, investments in LNG bunkering infrastructure in ports have really taken off. Quite a few public port authorities are playing a proactive role in facilitating the use of LNG as a marine fuel, often in close partnership with industrial actors [22].…”
mentioning
confidence: 99%
“…Unfortunately, there is no container transportation via railway networks between Bangladesh and India, but it is easily possible to start this under the banner of Bangladesh-Bhutan-India-Nepal-BBIN because of available rail track in the geographical area of BBIN. Moreover, researchers (Wang & Notteboom, 2015) found that port authorities are playing an important role in introducing Regional Innovation System (RIS) to establish social collaboration, knowledge creation, and the promotion of innovation. Here, innovation will help port authorities to facilitate and coordinate their own roles and typically seek meaningful extensions of their functions beyond their traditional roles under changing management.…”
Section: Innovation and Integrationmentioning
confidence: 99%